(untitled) (Research, Society and Development, 2020)
The objective is to study and analyze monthly and interannual rainfall fluctuations for São Bento do Una and Serra Talhada between (1920 to 2017) coupled with the techniques of frequency analysis and statistics. In São Bento do Una, rains are concentrated between December and July, with significant variations, observed each month, with months and years with zero rainfall or close to that, for 70.41% of the cases (69 years), rainfall was registered less than seven hundred mm. In Serra Talhada the rains were concentrated in December to May, with significant fluctuations with 82.65% of the cases (81 years old) presented rains below eight hundred mm. The rainfall climatic fluctuations were identified with irregularity and with concentration in some days of the year of extreme rains, causing setbacks to the population. The availability of water has repercussions in all economic activities, for the coexistence of situations caused by extreme climatic events, caused by the variability in the studied areas, it is essential to inform the rainfall behavior, incorporated into natural resources.